Makna Simbolik Tabu Pertunjukan Wayang Kulit Di Purbalingga, Karesidenan Banyumas, Jawa Tengah - Sugeng Priyadi (Mudra Jurnal Seni Budaya, 2007)
The taboo of leather puppet show in the rural community of Purbalingga shows a plurality of socio-culture laying on the puppet myth that has changed into local legend. The myth said that Purbalingga is the region of Kurawa. This belief leads to such social conflicts as cultural conflict, marriage conflict, spiritual conflict, and ethic conflict. These conflicts are so obviously seen in the area. The cultural conflicts have triggered the taboo of puppet show in the rural area of Purbalingga. The taboo can be perceived as the phenomena of 1) a violence ang regret to the local puppet legend making some story sacral and taboo to perform, 2) a knight ascetics having some different meanings. Arjuna lived as an ascetic to get a weapon and a glory in the battle, while Yudhistira did that to achieve ultimate nobility in life, and 3) an ethic violation concerned with the characters, of puppet in the legend of Ramayana and Mahabarata, that are regarded as the ancestors of Purbalingga community.